Aram and Israel during the Jehuite Dynasty - Hasegawa, Shūichi (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2012)
The Jehuite Dynasty was the longest dynasty in the history of the Northern Kingdom. Under the Jehuite kings, Israel was thrown into the arena of the regional political struggles and experienced the time of an unprecedented upheaval and then prosperity. This book is the result of a comprehensive study on this important dynasty that has never beenadequately discussed before. By consulting all the available epigraphical and archaeological sources, this study examines the historical authenticity of the biblical text and integrates the results into the historical discussion. Shuichi Hasegawa, Morioka University, Iwate, Japan.